ROLE IN Obstetric Acupuncture - Gondo, Harry Kurniawan (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2009)
Term " acupuncture" coming from Latin Ianguage âacusâ meaning needle, and punctura meaning to beÂ jabed. InChinese, thousands of last year, noted that sore army effect of arrow sometime get overÂ disease they which have suffer during through years. Emerge idea that, by jabing husk certain dot,Â disease will recover. Chineman start to imitate arrow effect, by jabing husk use needle. AcupunctureÂ represent important shares in traditional medication Chinese, including other technique like "kop", "moxibustion", masase ("Tuina"), and Chinese herb drug. More than 20 the last year of popularitasÂ acupuncture have mounted many shares in all the world. More and more interest to usage ofÂ acupuncture in practice midwifery. Organizational Health of World (WHO) express that there areÂ complete evidence which supporting conducive acupuncture therapy effect become important shares inÂ service of health of primary and that acupuncture have to fully integrated with conventional doctor.